2021
DOI: 10.1002/pri.1907
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' job satisfaction according to employment situation: Findings from an online survey in Austria

Abstract: Background and Purpose Physiotherapists are commonly working in self‐employed, employed, or in combined employed and self‐employed work arrangements. This study aimed at examining aspects of job satisfaction and predictors of physiotherapists' overall job satisfaction across those three types of work arrangements. Methods Austrian physiotherapists rated their overall job satisfaction as well as the importance and realisation of aspects of job satisfaction in a cross‐sectional online survey. Multiple linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…A study conducted among physiotherapists in Australia found that the career stage was strongly associated with job satisfaction with higher satisfaction levels among physiotherapists with more years of clinical practice which is similar to our findings 29 . Similar to our results, private practice owners had a better job satisfaction compared to physiotherapists working as employees 29,55 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A study conducted among physiotherapists in Australia found that the career stage was strongly associated with job satisfaction with higher satisfaction levels among physiotherapists with more years of clinical practice which is similar to our findings 29 . Similar to our results, private practice owners had a better job satisfaction compared to physiotherapists working as employees 29,55 …”
Section: Discussionsupporting
confidence: 89%
“…29 Similar to our results, private practice owners had a better job satisfaction compared to physiotherapists working as employees. 29,55 The only significant factor we found that was associated with job dissatisfaction was the annual income. That is, physiotherapists who had higher annual pay were at greater odds of reporting higher job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 78%
See 1 more Smart Citation
“…In other words, increased perceptions of networks were associated with greater job satisfaction. Networks in physiotherapy can be good for improving cross sectoral work, learning opportunities (Latzke et al, 2021) and is reported to be associated This study presented small to moderate correlations between BPS subscales. It might be linked with the perception of physiotherapists of learning and implementing the BPS approach that requires skills to comprehend the difference of this approach in order to applying their new skills.…”
Section: Key Resultsmentioning
confidence: 56%
“…It might be explained by heterogeneity of the participants in other studies while this study involved only rehabilitation professionals. The Ministry of Health of Ukraine is focusing on raising the awareness on implementation of the ICF approach in education and in continuous professional development of rehabilitation staff in Ukraine [29]. However, the REHAB project has demonstrated that education of physiotherapists in Ukrainian is more focused on problem or disease oriented (International Classification of Disease, ICD) but not to the goal oriented approach (ICF).…”
Section: Key Resultsmentioning
confidence: 99%